The educational innovators, 1750-1967 : V.2 : Progressive schools 1881-1967 - Stewart, W. A. C. (William Alexander Campbell), 1915- (Basingstoke, [England] : Macmillan, 2000)
The growth of schools 1889-1898. Merging into educational radicalism 1898-1918. New schools and Europe 1890-1918. Preface to the Post-War surgence. The post-war surgence: the twenties...
Keywords: Education; Educational change; Educational innovations; Education and state; Educational innovations -- England -- History; Educational change -- England -- History; Education and state -- England